A study on factors determining tourism products choices among the locals in Labuan FT / Sufrizal Yussof - Yussof, Sufrizal (Perpustakaan Tun Abdul Razak UiTM Caw Sabah, 2015)
In order to develop the tourism industry, service quality and tourist satisfaction has been a considerable goal for many countries. In fact, developing the tourist industry is the target of and government all over the world because it can generate GDP and jobs opportunities. Developing tourist industry in particular is desirable for all countries because it will benefit not only the industry itself but also generate a strong flow-through effect in other sectors such as retail transportation and construction. As such service quality, tourist satisfaction and attraction places the key factors of the successful in tourism industry. This is extremely important to clarify which dimensions affect the service quality and satisfaction in tourist industry. Also consequences of tourists· satisfaction and dissatisfaction should be studied to provide adequate knowledge for decision makers in this sector. This study tries to identify the factors affecting service quality and tourist satisfaction and explains consequences of the satisfaction and quality.